Reichsparteitag Nürnberg Ansichtskarte 1937 NSDAP Propaganda Richard... - Richard Borrmeister (Wikimedia Commons, 1937)
Carte postale ancienne issue de Wikimedia Commons. Titre: Reichsparteitag Nürnberg Ansichtskarte 1937 NSDAP Propaganda Richard BORRMEISTER Verlag Photo Hoffmann München Hitlerjunge Hitlerjugend Fahne Hitler Youth Nazi Rally Nuremberg Castle Postcard No known copyright restrictions 866426-0. " Nuremberg Party Rally " (Reichsparteitag Nürnberg). Postcard showing a uniformed member of the en:Hitler Youth (Hitler-Jugend, HJ) carrying a HJ-flag with the Nuremberg Castle in the background | painting signed R. Borrmeister | published by Verlag Photo-Hoffmann, Munich | Nazi Party (NSDAP) propaganda Nazi propaganda see Wikipedia: Children's propaganda in Nazi Germany Holocaust Encyclopedia: INDOCTRINATING YOUTH The Wiener Holocaust Library: A is for Adolf: Teaching German Children Nazi Values Jewish Virtual Library: Propaganda and Children During the Hitler Years etc.
Droits : Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château; Carte postale